2013
DOI: 10.1172/jci69660
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagic flux mediates acinar cell vacuole formation and trypsinogen activation in rodent models of acute pancreatitis

Abstract: For Figure 2A, the authors did not indicate that the two lanes were noncontiguous. The corrected figure and legend appear below.(A) LC3-I to LC3-II conversion (immunoblot) in pancreas of rats under conditions of fasting (for 17 hours) and pancreatitis (see Methods). ERK1/2 served as loading control. Lanes were run on the same gel but were noncontiguous.The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
135
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(153 citation statements)
references
References 69 publications
14
135
3
1
Order By: Relevance
“…These findings also stand in marked contrast to those reported in an earlier study in which Atg5 was ablated using Cre recombinase driven by the elastase promoter (13). In that study, no pancreatic injury was observed and the ATG5 deficiency was even claimed to ameliorate cerulein-induced pancreatic injury (13), a rather odd finding because cerulein-induced pancreatic injury entails inhibition of autophagic protein degradation (18). Notably, a more recent study demonstrated that Ptf1a-Cre-mediated Atg5 ablation does result in the development of pancreatitis (16), albeit not as severe as the pathology seen in Atg7 Δpan mice.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…These findings also stand in marked contrast to those reported in an earlier study in which Atg5 was ablated using Cre recombinase driven by the elastase promoter (13). In that study, no pancreatic injury was observed and the ATG5 deficiency was even claimed to ameliorate cerulein-induced pancreatic injury (13), a rather odd finding because cerulein-induced pancreatic injury entails inhibition of autophagic protein degradation (18). Notably, a more recent study demonstrated that Ptf1a-Cre-mediated Atg5 ablation does result in the development of pancreatitis (16), albeit not as severe as the pathology seen in Atg7 Δpan mice.…”
Section: Discussioncontrasting
confidence: 78%
“…Degradation of long-lived proteins, a major function of autophagy, is impaired during experimental pancreatitis, especially after administration of cerulein, which causes acinar cell vacuolization and excessive trypsinogen activation (18). Moreover, autophagic flux is reduced during pancreatitis due to defective cathepsinmediated processing of lysosomal proteases (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One early feature of AP is the accumulation of large autophagic vacuoles in pancreatic acinar cells (67,68). Autophagic flux is impaired in AP, which mediates acinar cell vacuole formation, trypsinogen activation, cell death and the inflammatory response (for example, inflammasome activation) (67,69,70), suggesting a protective role of autophagy in AP.…”
Section: Autophagymentioning
confidence: 99%
“…It has been found that pancreatitis stimulates autophagy induction and, at the same time, impairs late stages of autophagy (18). A defective autophagy could cause vacuole accumulation and trypsinogen activation, contributing to the development of pancreatitis (28).…”
Section: Hmgb1 Autophagy and Apoptosis In Pancreatic Cancermentioning
confidence: 99%